The Income of Salt Farmers in Madura: an Explanation of Profit-Sharing System - Echsan Gani; M. Boy Singgih Gitayuda (Trunojoyo University of Madura, 2020)
This study aimed to determine and analyze the level of income generating of salt farmers in Madura. This research was conducted with a qualitative approach. The qualitative approach in this study was to match empirical reality with the prevailing theory using descriptive methods. This research was located in the Sumenep Regency. Data collection techniques carried out by observation, interview, and documentation. Data analysis was performed descriptively-qualitatively. The results showed that the income of salt farmers in Madura was determined from the pattern of profit-sharing that had been chosen, namely the cost of salt production would be borne by landowners and sharecropper where the amount depended on the agreed pattern of profit-sharing. There were three pattern of profit-sharing between landowners and sharecropper in salt production, namely the pattern of dividing two (paron), the pattern of sharing for three (telon), and the pattern for five (leman). study aimed to determine and analyze the level of income generating of salt farmers in Madura. This research was conducted with a qualitative approach. The qualitative approach in this study was to match empirical reality with the prevailing theory using descriptive methods. This research was located in the Sumenep Regency. Data collection techniques carried out by observation, interview, and documentation. Data analysis was performed descriptively-qualitatively. The results showed that the income of salt farmers in Madura was determined from the pattern of profit-sharing that had been chosen, namely the cost of salt production would be borne by landowners and sharecropper where the amount depended on the agreed pattern of profit-sharing. There were three pattern of profit-sharing between landowners and sharecropper in salt production, namely the pattern of dividing two (paron), the pattern of sharing for three (telon), and the pattern for five (leman).